Predicting patient aggression against nurses in all hospital areas - Chapman, Rose; Perry, L.; Styles, I.; Combs, Shane (Mark Allen Publishing, 2009)
Workplace violence directed at nurses is an alarming phenomenon across the world. To intervene and manage these episodes as quickly as possible, nurses need to identify those factors that can alert them to the possibility that a violent event may occur. However, frameworks to help nurses predict episodes of workplace violence are limited. This article presents the findings of a study of nurses' experience of workplace vioelnce and identifies those factors and behaviours that nurses reported as indicating that an episode of workplace violence is likely to occur. A case study approach was used involving quantitative and qualitative data. One hundred and thirteen questionnaires were completed and 20 interviews were conducted in 2006. Nurses identified nine behaviours and factors that assist them to predict workplace violence. The first five factors comprising staring, tone of voice, anxiety, mumbling and pacing (STAMP) matched those identified in a previous study. However, the last four factors, comprising emotions, disease process, assertive/non-assertive behaviour and resources (EDAR) expand upon that study. Therefore, the acronym STAMPEDAR was used to classify the nine components. Being alert to these behaviours and factors may help nurses predict that an episode of workplace violence is likely to occur.